2020
DOI: 10.3390/condmat5030047
|View full text |Cite
|
Sign up to set email alerts
|

Broadband Anisotropic Optical Properties of the Terahertz Generator HMQ-TMS Organic Crystal

Abstract: HMQ-TMS (2-(4-hydroxy-3-methoxystyryl)-1-methylquinolinium 2,4,6-trimethylbenzenesulfonate) is a recently discovered anisotropic organic crystal that can be exploited for the production of broadband high-intensity terahertz (THz) radiation through the optical rectification (OR) technique. HMQ-TMS plays a central role in THz technology due to its broad transparency range, large electro-optic coefficient and coherence length, and excellent crystal properties. However, its anisotropic optical properties have not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…It was revealed that different physical processes-photocurrent surge effect due to the strong surface electric field induced band bending, the so-called photo-Dember effect, because of the spatial separation of the electrons and the holes due to their different mobilities, resulting in appearance of the electric field, second-order or the third-order susceptibilityrelated optical rectification or electrical field-induced optical rectification, respectively-can be found as responsible THz emission mechanisms in various semiconductors, such as radiation-damaged silicon-on-sapphire and low-temperature-grown, or ion-implanted GaAs, InGaAs, InAs, or GaAsBi semiconducting compounds [19]. Regarding investigated materials, one can note that the studies were not limited to semiconductors only; a special attention gained optical rectification-based THz emission from lithium niobate [20,21] and second-order nonlinear effects for THz generation in different type of organic crystals, like DAST, DSTMS, OH1, HMQ-TMS, and BNA [22][23][24][25][26]. It is worth noting air-plasma-based THz photonics approach when a high intensity femtosecond laser can induce plasma oscillations in air [27,28], which can emit broadband THz radiation [29,30].…”
Section: Compact Solutions In Thz Emittersmentioning
confidence: 99%
“…It was revealed that different physical processes-photocurrent surge effect due to the strong surface electric field induced band bending, the so-called photo-Dember effect, because of the spatial separation of the electrons and the holes due to their different mobilities, resulting in appearance of the electric field, second-order or the third-order susceptibilityrelated optical rectification or electrical field-induced optical rectification, respectively-can be found as responsible THz emission mechanisms in various semiconductors, such as radiation-damaged silicon-on-sapphire and low-temperature-grown, or ion-implanted GaAs, InGaAs, InAs, or GaAsBi semiconducting compounds [19]. Regarding investigated materials, one can note that the studies were not limited to semiconductors only; a special attention gained optical rectification-based THz emission from lithium niobate [20,21] and second-order nonlinear effects for THz generation in different type of organic crystals, like DAST, DSTMS, OH1, HMQ-TMS, and BNA [22][23][24][25][26]. It is worth noting air-plasma-based THz photonics approach when a high intensity femtosecond laser can induce plasma oscillations in air [27,28], which can emit broadband THz radiation [29,30].…”
Section: Compact Solutions In Thz Emittersmentioning
confidence: 99%
“…Design strategies have been also discussed and some examples have been presented and analyzed. D'Arco et al, in their contribution [21] measured the complex refraction index of one HMQ-TMS (2-(4-hydroxy-3-methoxystyryl)-1-methylquinolinium 2,4,6-trimethyl benzenesulfonate) single crystal from THz to UV, observing a remarkable anisotropy, strongly attenuated at long wavelengths. The HMQ-TMS is a recently discovered anisotropic organic crystal that can be exploited for the production of broadband high-intensity THz radiation through the optical rectification technique.…”
Section: Discussionmentioning
confidence: 99%
“…In the last two decades, many efforts have been made to improve THz technology, e.g., THz sources and detectors [56][57][58][59][60][61][62][63][64][65][66][67][68][69], discovering new materials with strong THz response [70][71][72][73] and new customizable, flexible and compact devices for spectroscopy [74].…”
Section: Thz Technology For Protein Spectroscopymentioning
confidence: 99%